Co-production of urban climate planning: Insights from the Barcelona Climate Plan. (November 2020) - Satorras, Mar; Ruiz-Mallén, Isabel; Monterde, Arnau; March, Hug
Abstract: Climate policy co-production represents an emerging institutional arrangement promising to better and fairly involve societal actors in resilience policy-making. Little evidence exists, however, on how climate policy co-production is understood, planned and performed in cities. This article sheds light on these co-production processes through an in-depth analysis of the case study of the Barcelona Climate Plan. While traditional forms of public engagement such as face-to-face workshops served to collect most proposals from organizations, new tools such as the digital platform resulted in increased lay citizen involvement and process transparency. Participants, including organizers of the co-production process, did not share a clear understanding of what co-production was about, which can endanger the fulfilment of the goals. These findings shed light over effective and limiting procedural and conceptual aspects for co-production of urban climate policies and guide a critical discussion over the added value and the transformative potential of the co-production approach to reframe urban climate resilience planning in cities. Highlights: An in-depth analysis of the co-production process leading to the Barcelona Climate Plan is presented Tools for public engagement involved interested organisations effectively but failed in engaging lay citizens The digital platform provided transparency and promoted lay citizen participation in climate resilience decision-making Contrasting views of the co-production process resulted in confusion of goals and deterred from empowerment The transformative potential of co-production was limited by institutional reluctance, time and unclear expectations